A New High Opening Trawl For Veraval Waters - KUNJIPALU, K K; BOOPENDRANATH, M R; GOPALAKRISHNAN, K; KUTTAPPAN, A C (Fishery Technology, 2017)
The newly developed 25m high opening trawl possesses the properties of a high rising bottom trawl and a semi-pelagic trawl. The new gear is effective for the capture of demersal and semi-pelagic fishes. The net offered more horizontal opening and less resistance with significantly high catch of ribbon fish when compared with bulged belly trawl.